Is Small Beautiful? Financial Structure, Size and Access to Finance - Beck, Thorsten; Demirgüç-Kunt, Asli; Singer, Dorothe (2012)
Combining two unique data sets, this paper explores the relationship between the relative importance of different financial institutions and their average size and firms' access to financial services. Specifically, the authors explore the relationship between the share in total financial assets and average asset size of banks, low-end financial institutions, and specialized lenders, on the one hand, and firms' access to and use of deposit and lending services, on the other hand. Two findings stand out. First, the dominance of banks in most developing and emerging markets is associated with lower use of financial services by firms of all sizes. Low-end financial institutions and specialized lenders seem particularly suited to ease access to finance in low-income countries. Second, there is no evidence that smaller institutions are better in providing access to finance. To the contrary, larger specialized lenders and larger banks might actually ease small firms' financing constraints, but only at low levels of gross domestic product per capita.